Social media engagement and occupational stress (Vallis Aurea, 2019)
The study attempted to recognized the relationship between social media engagement and occupational stress of millennial employees in private sector, Sri Lanka. It was further evaluated whether the gender moderate the relationship between above two variables. Population of the study is millennial employees who are using Facebook for social media engagement in private sector organizations and used cluster and convenience sampling techniques to select sample units. The sample size of this study was 68 employees. This study mainly based on primary data which collect through a survey. According to survey, 26.47% of employees spend one to two hours for social media and 22.6% respondents used Social Media for update on friend’s activity. The study findings revealed that there is a significant moderate positive relationship between social media engagement and occupational stress.Further, it was indicated that relationship between social media engagement and occupational stress was not moderated by the gender. Hence, the study can be concluded that there is a moderate relationship between two factors and gender differences do not strengthen or weaker the relationship between social media engagement and occupational stress.